Effects of acute environmental and handling exposure on physiology and fillet quality of market‐sized Channel Catfish. (31st January 2020) - Allred, Shay; Shao, Wenjie; Jones, Jacob H.; Schilling, M. Wes; Baker, Beth H.; Allen, Peter J.
Abstract: Catfish Ictalurus spp. are subjected to stressful conditions during harvest, which may be linked to fillet coloration and quality. Poor water quality in ponds, socks or hauling tanks, as well as handling stress, have been suggested to cause red fillets in catfish; however, chronic exposure has not resulted in red fillets. Short‐term occurrences of extreme poor water quality, particularly low dissolved oxygen, high carbon dioxide and high temperature, may occur in ponds or during harvest. Therefore, market‐sized Channel Catfish Ictalurus punctatus were acutely exposed (12 hr) to one of the three water quality treatments while confined during a simulated socking procedure and evaluated for stress responses by means of change in blood parameters and fillet quality. In fish subjected to the extreme treatment, hematocrit, plasma cortisol, glucose and lactate levels increased, with 22% mortality, indicating highly stressful conditions. In fish subjected to moderate and typical (control) treatments, cortisol increased but a lack of change or decrease in glucose and lactate indicated minimal anaerobic metabolism. Only one red fillet was produced by the extreme treatment and two by the typical treatment; therefore, the results suggest red fillets are not a product of poor water quality compounded by handling during harvest.